A historiografia do cangaço revisitada : três matrizes interpretativas - (:unkn) unknown (Universidade Estadual de Goiás, 2021)
This work has as main objective to demonstrate the existence of interpretative matrixes in the historiography of the Cangaço. This work aims to demonstrate the existence of interpretative matrices in the historiography of the "Cangaço". This premise took us to the field, where we started to get to know the specialized bibliography and to recognize interpretative patterns throughout the bibliography, which made us infer the possibility of seeing a preponderance in some interpretations in relation to the others regarding the social nature of the Cangaço. Thus, we chose three names that stood out throughout the bibliography: Gustavo Barroso, Rui Facó, and Frederico Pernambucano de Mello. In the research that follows, we highlight each of these respective authors emphasizing their avant-garde contributions to the Cangaço, thus understanding the written text as representation. In the wake of this process, we rescue the social place of each of these authors in order to understand the social place in which such research was materialized, as well as to whom it was intended. Finally, the efficacy of the research would pass through the sieve of other researchers of the "Cangaço", who would made the interpretation of such theories, making them apt to be called interpretative matrices.
The historiography of the Cangaço revisited : three interpretative matrices
Keywords: Cangaço; Representação; Lugar social; Matriz interpretativa; Historiografia.; Cangaço; Representation; Social place; Interpretative matrix; Historiography; CIENCIAS HUMANAS::HISTORIA